Slovo i obred: tălkuvanijata na liturgijata v konteksta na drugi kulturno blizki tekstove na slavjanskoto srednovekovie - Minczew, Georgi ‎ (Poredica Istorija i knižnina, 2011)
Engl. Zsfassung u.d.T.: Word and rite : commentaries on the holy liturgy in the context of other culturally related texts in the Slavonic Middle Ages